Effect of population density on growth and production of hybrid maize. Issue 1 (November 2021) - Suwardi,; Syafruddin,; Aqil, Muhammad; Efendi, Roy; Bunyamin, Z.
Abstract: One of the strategies to increase maize production is by selecting the proper combination among variety and planting density. The plant density population experiment was carried out to identify the candidate of maize variety that has high productivity with limited sunlight levels. Our hypothesis was how the erect leaf maize type can get optimal sunlight and affect the productivity. The study was conducted in IP2TP Bajeng, Gowa, South Sulawesi from March to June 2020. This study was designed under split plot design where spacing or plant density as the main plot with 3 levels of treatment (70 cm x 20 cm (population 71, 428 plants/ha), 60 cm x 20 cm (population 83, 333 plants/ha) and 50 cm x 20 cm (population 100, 000 plants/ha). Furthermore, eight genotypes of hybrid maize (ERC 01, ERC 02, ERC 03, ERC 04, ERC 05, ERC 06, ERC 07, ERC 08), including control varieties (JH 45 and Pioneer 36) were treated as the sub-plots. The results indicated that the maize yield increase in line with the increase in plant population. The plant's spacing of 70 x 20 cm with 100, 000 plants/ha was produced 10.61 t/ha, significantly higher than other treatments.